(untitled) (Multidisciplinary Journal of Science and Technology, 2023)
food safety is an important element of national security, therefore its provision is one of the most important tasks of any country. The strategy and tactics of ensuring food security of the country should be based on the results of an impartial assessment of its level in the cross-section of regions. In the article, the criteria and indicators for evaluating the integral indicator of food security in the region, that is, five criteria (physical and economic availability of food, nutritional balance, food quality and safety, stability of the food system), each of them it is proposed to describe one, a set of indicators is defined.